IMPLEMENTASI TIGA KATA AJAIB DALAM PEMBENTUKAN KARAKTER SISWA DI SDIT AL-AZHHAR BOGOR - Nadia Aulia; Suhendra; Yono Yono (Universitas Pahlawan Tuanku Tambusai, 2022)
This thesis aims to determine (1) the implementation of the Three Magic Words in the Character Building of Students at SDIT Al-Azhhar Bogor. (2) The Impact of the Implementation of Three Magic Words in the Character Building of Students at SDIT Al-Azhhar Bogor. This study uses a qualitative approach that is descriptive of the type of field research. It was carried out from September 21, 2022 to September 29, 2022. The research location was at SDIT Al-Azhhar Bogor. In the data collection procedure the author uses observation techniques, interview techniques and documentation techniques. Meanwhile, in data analysis, researchers used data collection, data reduction, data presentation and drawing conclusions. The results of this study found that (1) The implementation of the habituation of three magic words in the formation of students' character at SDIT Al-Azhhar Bogor is the way to apply them, among others, the habit of saying three magic words (sorry, please and thank you) the teacher tells the importance of the three magic words and makes notifications which is like an appeal pamphlet, other than that it provides examples and reminds each other. (2) The impact of the implementation of the habituation of three magic words in the formation of students' character at SDIT Al-Azhhar Bogor, namely, Obedience to God, namely students have morality towards teachers by applying the three magic words (sorry, please and thank you). Patience is being able to control emotions when fighting so that they can forgive each other. Unselfish in word and deed. Can reach out to help each other. And give thanks in every gift. Keywords: Habituation, Three Magic Words, Character Education